Anti-inflammatory effects of neutral lipids, glycolipids, phospholipids from Halocynthia aurantium tunic by suppressing the activation of NF-κB and MAPKs in LPS-stimulated RAW264.7 macrophages - A-yeong Jang; Weerawan Rod-in; Chaiwat Monmai; Gyoung Su Choi; Woo Jung Park (PLoS ONE, 2022)
Halocynthia aurantium is a marine organism that has been considered a promising source for bio-functional materials. Total lipids were extracted from H. aurantium tunic, and then they were separated into neutral lipids, glycolipids, and phospholipids. In the present study, fatty acid profiles of three lipids and their anti-inflammatory effects in RAW264.7 cells were investigated. Among the lipid classes, phospholipids showed the diversity of fatty acid constituents, compared with the glycolipids and neutral lipids. Three lipids contain different contents of fatty acids depending on the kinds of lipids. The most contents were saturated fatty acids (SFAs, 53–69% of the fatty acids) and monounsaturated fatty acids (MUFAs, 15–17% of fatty acids) and polyunsaturated fatty acids (PUFAs, 14–32% of fatty acids) are followed. H. aurantium lipids not only dose-dependently inhibited nitric oxide production but also reduced the expression of inflammatory cytokine genes such as TNF-α, IL-1β, and IL-6 in LPS-stimulated macrophages. It was also demonstrated that the expression of COX-2 was dose-dependently suppressed. Moreover, H. aurantium lipids decreased phosphorylation of NF-κB p-65, p38, ERK1/2, and JNK, suggesting that three lipids from H. aurantium tunic provide anti-inflammatory effects through NF-κB and MAPK signaling. These results indicate that H. aurantium is a potential source for anti-inflammation.